2017
DOI: 10.1016/j.ijsu.2017.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Retroinfundibular laparoscopic cholecystectomy versus standard laparoscopic cholecystectomy in difficult cases

Abstract: In difficult cholecystectomy, RI approach is feasible and safe alternative to SLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Several studies have shown how the "fundus-first" technique is associated with reduced rates conversion rate and iatrogenic complications (including BDIs) during difficult operations, such as in cases of severe AC [49][50][51][52], although the risk of vascular and biliary injuries cannot be completely eliminated [10,53]. It is essential to recognize approaching areas of danger during LC and, in response, stop dissection and change to a bailout procedure (STC or cholecystostomy) to minimize the need for conversion and to reduce the risk of BDI [48,[54][55][56]. However, STC is associated with significantly more surgical site infections, a need for re-interventions, and a longer hospital stay than total cholecystectomy [57].…”
Section: Bailout Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown how the "fundus-first" technique is associated with reduced rates conversion rate and iatrogenic complications (including BDIs) during difficult operations, such as in cases of severe AC [49][50][51][52], although the risk of vascular and biliary injuries cannot be completely eliminated [10,53]. It is essential to recognize approaching areas of danger during LC and, in response, stop dissection and change to a bailout procedure (STC or cholecystostomy) to minimize the need for conversion and to reduce the risk of BDI [48,[54][55][56]. However, STC is associated with significantly more surgical site infections, a need for re-interventions, and a longer hospital stay than total cholecystectomy [57].…”
Section: Bailout Proceduresmentioning
confidence: 99%
“…55 Unit of Gastroenterology and Endoscopy, Maggiore Hospital, Bologna, Italy. 56 Department of Surgery, UPMC, University of Pittsburg, School of Medicine, Pittsburg, USA. 57 General Surgery, Liver Transplant Unit, Hospital Italiano de Buenos Aires, Buenos Aires, Argentina.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…BDI was not specified. A prospective, non-randomized trial compared results between patients with preoperative predictors for difficult cholecystectomy based on an objective scoring system [87]. Sixty-five patients who underwent a version of subtotal laparoscopic cholecystectomy had no BDI and one conversion.…”
Section: Laparoscopic Subtotal Cholecystectomymentioning
confidence: 99%
“…In literature, Sewefy et al mentions operative time to be (114±10 minute), which was comparable with our study. 4 In a study by Atta the operative time taken by experienced surgeon for laparoscopic cholecystectomy is 30-70 minutes. The gall bladder wall thickness of≥4mm was taken as difficult operation.…”
Section: Calculous Cholecystitismentioning
confidence: 99%
“…It is because of subjectivity. Studies have used preoperative scoring parameters to define a difficult operation [4][5][6]. However, we have not used them in our study.…”
mentioning
confidence: 99%